(untitled) (Theatrum historiae, 2014)
This study focuses on the analysis of narrative patterns of the Prague Spring in the collective memory of former members of the Czechoslovak People ́s Army, who had been made redundant as result of their negative attitude towards the intervention of Warsaw Pact troops into Czechoslovakia in August 1968. The analysis is based on interviews that were taken by oral history method. The subjects of the analysis are specific narrative method of construction, interpretation formulas, stereotypes and relationship of these elements to the collective memory of the selected group of narrators.